2017
DOI: 10.1016/j.jjcc.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Safety of transradial diagnostic cardiac catheterization in patients under oral anticoagulant therapy

Abstract: Performing a transradial diagnostic cardiac catheterization without removal of the oral chronic anticoagulation appears safe in patients under acenocumarol therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…22 In our study 12.7% cases of group A developed haematoma as compared to 22.2% of group B (p=0.15) Although we did not rule out prior use of anticoagulation, but a study found no difference in rate of haematoma formation in patients with history of anticoagulation 5% as compared to 4.6% in patients without prior use who underwent radial artery catheterization. 23 Radial artery haematoma was reported in only 2.3% cases who underwent radial artery catheterization, although the study was questionnaire based. 24 Mean time required for group A patients was 71.0 ± 26.4 minutes while of group B was 96.5 ± 62.3 minutes, which was statistically significant, p= 0.31.…”
Section: Groupmentioning
confidence: 97%
“…22 In our study 12.7% cases of group A developed haematoma as compared to 22.2% of group B (p=0.15) Although we did not rule out prior use of anticoagulation, but a study found no difference in rate of haematoma formation in patients with history of anticoagulation 5% as compared to 4.6% in patients without prior use who underwent radial artery catheterization. 23 Radial artery haematoma was reported in only 2.3% cases who underwent radial artery catheterization, although the study was questionnaire based. 24 Mean time required for group A patients was 71.0 ± 26.4 minutes while of group B was 96.5 ± 62.3 minutes, which was statistically significant, p= 0.31.…”
Section: Groupmentioning
confidence: 97%
“…A recent prospective observational study compared acenocoumarol continuation versus discontinuation in 489 patients undergoing trans-radial diagnostic catheterization. The study concluded that continuation of chronic OAT appears safe during trans-radial diagnostic catheterization [ 95 ]. Similarly, in a prospective study, Sanmartín M et al concluded that the trans-radial approach appears to be a safe option and could be the technique of choice for patients continuing long-term acenocoumarol therapy as it eludes the problems and complications associated with the withdrawal of OAT [ 96 ].…”
Section: Anticoagulationmentioning
confidence: 99%
“…A recent paper by Gallego-Sanchez et al evaluated the safety of transradial catheterization in patients on anticoagulation and concluded that while patients on anticoagulation were generally older, no complications or statistically significant difference in hematoma formation was seen in the first 24 hr suggesting that this may be a safe and effective way to perform cardiac catheterization in patients on anticoagulation. 2 Most recently, based on the WOEST trial (and PIONEER AF-PCI and REDUAL-PCI trials for direct oral anticoagulants), it is gaining favor to drop aspirin for double therapy rather than triple therapy. Bleeding episodes were seen in 54 (19%) patients receiving double therapy and in 126 (44%) receiving triple therapy (hazard ratio [HR] 0.36, 95% CI 0.26-0.50, P < 0.0001).…”
Section: The Median International Normalized Ratio (Inr) Was 21 and mentioning
confidence: 99%
“…There are several papers, which suggest that bleeding rates are lower with radial access, particularly in patients who are older, female, and have more comorbid conditions, so it may be reasonable to consider access site in cases where full anticoagulation is present. A recent paper by Gallego‐Sanchez et al evaluated the safety of transradial catheterization in patients on anticoagulation and concluded that while patients on anticoagulation were generally older, no complications or statistically significant difference in hematoma formation was seen in the first 24 hr suggesting that this may be a safe and effective way to perform cardiac catheterization in patients on anticoagulation …”
mentioning
confidence: 99%